Improving prenatal HIV screening with tailored educational interventions: an approach to guideline implementation. Issue 6 (10th August 2010) - Prairie, B A; Foster, T
Abstract : Background: A healthy, uncomplicated pregnancy undergoes approximately 13 tests performed over an average of 12.5 prenatal visits. Published rates of compliance with routine prenatal testing are generally >90%, with lower rates for newer tests or those that require additional inputs prior to ordering. New CDC guidelines for prenatal HIV testing highlight the importance of prenatal testing and motivated the authors to explore our routine prenatal testing performance. The authors found the conceptual framework of simple/complicated/complex problems in healthcare helpful in understanding the rates for tests and for developing interventions. Methods: The setting for this work was a single, rural, academic tertiary care centre. Baseline rates of four routine prenatal tests (HBsAg, 1 h GTT, GBS, HIV) were determined by analysing 12 months of data from a web-based delivery registry. All rates were >90% except HIV, which was 79.2%. Process mapping and discussions with ordering providers were performed to plan the improvement intervention. Targeted educational interventions specific to each ordering provider type were followed by audit and feedback. HIV testing rates were monitored and analysed monthly using process control charts. Results: The HIV testing rate increased significantly from 79.2% to 94.2%. Rates greater than 90% were maintained for 10 of 11 months reported. Conclusions: Targeted educational interventions combined with audit and feedback can increase rates of routine testing successfully in an outpatient setting. These interventions can be used to improve implementation and compliance with new guidelines when informed by an understanding of local context and processes coupled with an appropriate conceptual framework.